Osnove konstruiranja: Učbenik - Pehan, Stanislav; Glodež, Srečko; Kramberger, Janez (University of Maribor Press, 2021)
Basics of Mechanical Design: Textbook. The textbook presents the theoretical basis of design of machine parts and structural elements, which are supplemented at certain places with some practical examples. At the beginning, some basic concepts in mechanical design are explained, and then the individual stages of design (planning, conceptualization, preliminary design and detailed design) are discussed in detail. This, together with general guidelines for design and structural materials, represents the central part of the textbook. Finally, the design tools and technical legislation in the field of design are briefly presented.The textbook is intended for mechanical engineering students in the subjects Basics of Design and Methodology of Design, but it is also useful in subjects of related content. As there are many practical examples in the textbook, it is also a useful tool for design engineers when designing in everyday technical practice.